2020
DOI: 10.1101/2020.10.21.348144
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RIT2 reduces LRRK2 kinase activity and protects against alpha-synuclein neuropathology

Abstract: In Parkinson's disease (PD) misfolded alpha-synuclein (aSyn) accumulates in the substantia nigra, where dopaminergic neurons are progressively lost. The mechanisms underlying aSyn pathology are still unclear but hypothesized to involve the autophagy lysosome pathways (ALP). LRRK2 mutations are a major cause of familial and sporadic PD, hyperactivate kinase activity and its pharmacological inhibition reduces pS129-aSyn inclusions. We observed selective downregulation of the novel PD risk factor RIT2 in G2019S-L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…Known molecular mechanisms that could explain the observed pH-eQTL are lacking. One exception is a recent study of interactions between RIT2 and LRRK2 (Obergasteiger et al, 2021). Using postmortem gene expression data, Obergasteiger et al observed down-regulation of RIT2 in the substantia nigra of PD cases.…”
Section: Discussionmentioning
confidence: 99%
“…Known molecular mechanisms that could explain the observed pH-eQTL are lacking. One exception is a recent study of interactions between RIT2 and LRRK2 (Obergasteiger et al, 2021). Using postmortem gene expression data, Obergasteiger et al observed down-regulation of RIT2 in the substantia nigra of PD cases.…”
Section: Discussionmentioning
confidence: 99%